PEMANFAATAN TANAMAN PANGAN OLEH MASYARAKAT DESA SUNGAI MUNTIK KABUPATEN SANGGAU - Fathul Yusro; H A Oramahi; Yeni Mariani; Efitanus Angga Windra (Universitas Tanjungpura, 2023)
Forests have a diversity of biological resources that have the potential to be used as a food source. The purpose of this study was to analyze the plants used as a food source by the people in Sungai Muntik Village, Sanggau Regency. The method used is a survey with a purposive sampling technique of data collection through interviews and observation of plant species in the field. The data obtained were analyzed to determine the number of plant families used, the form of utilization of foods plants, the parts used, the processing method, and the use value (UV). Result of research showed that the community of Sungai Muntik village used 64 species of plants included in 34 families as a food source. The most commonly used plant families are Poaceae and Zingiberaceae, each with 6 species. Seven food groups are used, such as vegetables, fruits, tubers/cereals, flavorings, drinks, food coloring, and food plants with medicinal properties. The part of the plant most often used as a food ingredient is the fruit with a proportion of 48.54% and is generally processed by cooking (61.77%). The plant with the highest Use Value (UV) is Oryza sativa (rice) with a UV value of 1, followed by Capsicum frutescens (chili peppers) with a value of 0.98, and Manihot utilissima (cassava) with a value of 0.97. Keywords: community, foods plant, forest, Muntik village, use value AbstrakHutan memiliki keanekaragaman sumber daya hayati yang berpotensi untuk dijadikan sebagai sumber pangan. Tujuan penelitian ini adalah untuk menganalisis jenis-jenis tumbuhan yang dimanfaatkan sebagai sumber pangan oleh masyarakat di Desa Sungai Muntik, Kabupaten Sanggau. Metode yang digunakan adalah survei dengan teknik pengumpulan data secara purposive sampling melalui wawancara dan observasi jenis tumbuhan pangan di lapangan. Data yang diperoleh dianalisis untuk mengetahui besarnya famili tumbuhan yang digunakan, bentuk pemanfaatan bahan pangan, bagian yang digunakan, cara pengolahan dan use value (UV). Masyarakat Desa Sungai Muntik menggunakan 64 jenis tumbuhan yang termasuk dalam 34 famili sebagai sumber pangan. Famili tumbuhan yang paling umum digunakan adalah Poaceae dan Zingiberaceae, masing-masing dengan 6 jenis. Ada tujuh kelompok makanan yang digunakan, seperti sayuran, buah-buahan, umbi/sereal, penyedap rasa, minuman, pewarna makanan, dan tumbuhan pangan berkhasiat obat. Bagian tumbuhan yang paling sering digunakan sebagai bahan makanan adalah buah dengan proporsi 48,54%, dan umumnya diolah dengan cara dimasak (61,77%). Tumbuhan dengan nilai Use Value (UV) tertinggi adalah Oryza sativa (padi) dengan nilai UV sebesar 1, disusul oleh Capsicum frutescens (cabe) dengan nilai 0,98 dan Manihot utilissima (ubi kayu) dengan nilai 0,97.Kata kunci: Desa Sungai Muntik, hutan, masyarakat, tumbuhan pangan, use value